Pengaruh Gaya Hidup, Sikap Keuangan, dan Literasi Keuangan Terhadap Kepuasan Keuangan Generasi Z di Jabodetabek - Alda Aurelia Artagita; Umi Widyastuti; Meta Bara Berutu (Teewan Journal Solutions, 2026)
This study aims to analyze the influence of lifestyle, financial attitude, and financial literacy on financial satisfaction among Generation Z in Jabodetabek. Generation Z, as digital natives, is highly exposed to financial technology and consumer trends that can affect their financial well-being. This research adopts a quantitative descriptive approach using a survey method and Google Form questionnaire to collect data from 170 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that lifestyle, financial attitude, and financial literacy have a positive and significant influence on financial satisfaction. The results suggest that a balanced lifestyle, a positive attitude toward finance, and adequate financial literacy contribute to a higher level of financial satisfaction among Generation Z in urban areas.